Materials for history? Publishing records as an historical practice in eighteenth- and nineteenth-century England - Riordan, M (University of Chicago Press, 2017)
Throughout the eighteenth and nineteenth centuries a large number of historical records were published in a wide variety of forms, most of which can be described as being part of wider historical and antiquarian practices. Taking the publishing of record editions as itself an historical practice, this essay surveys the varying people, practices and purposes involved before discussing a number of continuities and changes in the practice across two centuries. It will show how records publications were not only access driven, but also concerned with the preservation of records, and that they influenced archival practices, changing the way that archival collections were ordered and arranged. The essay will also argue that the place of record publications in wider historical practice changed from being one amongst a wide variety of practices used to engage with the past to a much more restricted role as an auxiliary practice making sources available to narrative historians.